Flexible rotary reduction of tube tips by dies with relief surfaces for attaining high forming limit and productivity. Issue 1 (2015) - Kuboki, Takashi; Abe, Mitsumasa; Yamada, Yohei; Murata, Makoto
Abstract This paper presents an innovative flexible rotary reduction method of tube tip using a relieved die. The relieved die is composed of contact surfaces and relief surfaces, which are connected smoothly. The proposed method realizes both high formability and productivity without heat generation so as to maintain the material strength. Diversified shapes of products used for catalyst cases, exhaust manifolds, pipe connections and so on would be able to be manufactured by changing the die cone angle, the raw-tube shape, the eccentricity between the die and tube axes and the inclination of the die.